(untitled) (MAUSAM, 1965)
Electrical conductivity of monsoon rain water was measured at Poona for nine complete rain periods. Conductivity and rate of rainfall vary in opposite phase during the course of a shower indicating that larger raindrops are more dilute than the smaller Ones. The average relation between the conductivity and the intensity of precipitation is found to be of the form, conductivity Ct; (Intensity)-n, where n is a. positive constant.